A Rare Case of Staphylococcal Toxic Shock Syndrome in a Neonate - Nipun Shrestha; Alisha Joshi; Yumiko Hayashi; Dhruba Shrestha; Bhim Gopal Dhoubhadel (Case Reports in Infectious Diseases)
Staphylococcus toxic shock syndrome (TSS) is not well described in neonates. The present criteria for diagnosis of TSS have not yet been validated in neonates. Here, we present a case of a 13-day-old female baby who presented with acute kidney injury (AKI). She had a pus-draining lesion on the head, and the pus grew Staphylococcus aureus. Based on the clinical criteria of fever, desquamation, hypotension, and AKI and laboratory criteria of absence of growth of any organisms in blood and cerebrospinal fluid, we diagnosed the case as TSS. She was treated with antibiotics, oxygen, and fluids, along with inotropic support and mechanical ventilation, and she recovered fully and was discharged on day 17 of admission. As there is no single test to diagnose TSS and it is uncommon in neonates, physicians should be familiar with the clinical presentation of the disease to make early diagnosis.